Papel da Capsaicina de uso tópico em modelo murino de colite experimental induzida por dextrano sulfato de sódio (DSS) - Elandia Aparecida dos Santos (2022)
Capsaicin, a pungent compound of peppers is described as a potent anti-inflammatory agent, besides having antioxidant and antimicrobial properties, modulating the immune system and microbiota. Our objective was to evaluate the effect of topical use of capsaicin on the improvement of inflammation and epithelial barrier function in experimental colitis induced by dextran sodium sulphate (DSS). For this, C57/BL6 mice, healthy or with DSS induced colitis received or not capsaicin cream at 0.075% for 6 days. Our results showed for the first time that capsaicin cream reduced weight loss, colon shortening and diarrhea, all typical signs of colitis. The pharmacokinetics of radioactive technetium labelled capsaicin shows that the capsaicin cream applied to the back of the animal reaches the colon and can act directly on that site. The use of capsaicin cream led to the improvement of epithelial barrier function, preserving proteins of thigh, adherent junctions and desmossomes. A lower frequency of CD4 T cells (RORT, LAP e Treg) was seen in the cecal lymph nodes of the capsaicin treated animals. We also observed that the group treated with capsaicin cream improved the profile of short-chain fatty acids in the cecum. Finally, we observed higher expression of the capsaicin receptor TRPV1 in the groups receiving capsaicin cream. In conclusion, our results suggest that topical administration of capsaicin may be a promising adjuvant in the treatment of colitis, reducing inflammation and improving intestinal barrier function.